Sustainable Food Drying Enhancing Efficiency, Nutrition, and Waste Reduction in Food Production - Nnadikwe Johnson; Iheme Chigozie; Momoh abdulazeez adeyem; Stephen Oyelami (Journal Majelis Paspama, 2026)
Food drying is crucial for ingredient innovation and product development. Recent breakthroughs in pretreatments, processes, and technologies like microwave and ultrasound drying have transformed the industry, boosting efficiency, preserving nutrients, and reducing waste. These innovations promote sustainability, enabling resource-efficient and technologically advanced food production. Wider adoption of these cutting-edge technologies is crucial to maximize their impact. By embracing modern drying methods, businesses can enhance sustainability, improve production, and increase profitability while preserving nutritional value. This study bridges research and practice, showcasing the benefits of modern drying technologies for sustainable food systems. By adopting these innovations, businesses can foster sustainability, reduce waste, and gain a competitive edge, paving the way for a more efficient and sustainable food future